2019
DOI: 10.1177/1753425919840424
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TLR2, TLR3, TLR4, and TLR7 on pulmonary lymphocytes of Schistosoma japonicum-infected C57BL/6 mice

Abstract: Despite the paramount role of TLRs in the induction of innate immune and inflammatory responses, there is a paucity of studies on the role of TLRs in Schistosoma japonicum infection. Here, we observed obvious infiltration of inflammatory cells in S. japonicum-infected C57BL/6 mouse lungs. Expression and release of IFN-γ, IL-4, and IL-17 were significantly higher in pulmonary lymphocytes from infected mice compared with control mice in response to anti-CD3 plus anti-CD28 mAbs. Higher percentages of TLR2, TLR3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Additionally, eggs could deposit in the lung and wall of intestinal tract of animals, and induced related diseases [35]. At 5–6 weeks after infection, obviously egg granulomatous inflammation could be detected in the liver and lung [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, eggs could deposit in the lung and wall of intestinal tract of animals, and induced related diseases [35]. At 5–6 weeks after infection, obviously egg granulomatous inflammation could be detected in the liver and lung [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Many kinds of immune cells recognize pathogen associated molecular patterns (PAMPs) of schistosoma and modulate the immune response by expressing TLRs [ 26 , 33 ]. Some of TLRs were found expressed on MDSCs during the immune response induced by invaded pathogens [ 32 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pattern recognition receptors (PRRs), such as Toll-like receptors (TLRs), have been reported to recognize pathogen-associated molecular patterns (PAMPs) of Schistosoma and modulate the immune response [ 25 , 26 ]. TLR7 is an endosomal TLR that recognizes single-stranded RNA (ssRNA) and mediates early innate immune responses to viruses, bacteria and malaria [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qu demonstrated that TLR3 is the primary molecule which modulates the activation and function of NK cells during Schistosoma japonicum (S. japonicum) infection in mice (Qu et al 2018). The expression levels of TLR3 on different pulmonary lymphocytes were increased after S. japonicum infection (Chen et al 2019). T. spiralis can also modulate the immune response by regulating the expression of TLRs and their signaling pathways (Yu et al 2013).…”
Section: Discussionmentioning
confidence: 99%